Filth : A Novel - Welsh, Irvine (London Jonathan Cape, 1998)
Detective Sergeant Bruce Robertson is winding down at work and gearing up for Christmas with a week of sex and drugs in Amsterdam. There are irritating distractions, though, including a missing wife, a nagging cocaine habit, a dramatic deterioration in his genital health, and a string of extra-marital affairs. The last thing he needs is a messy murder to solve.
Keywords: Scotland--Edinburgh -- Murder -- Cocaine abuse